Beyond RPV Design Life - Ballesteros, A.; Garcia, G.; Bogede, L.; Bros, J. (Проблемы прочности, 2004)
A set of standard reactor pressure vessels (RPV) surveillance programs for monitoring the design life (up to 40 years of reactor operation) have been analyzed. In view of the improved test methods and embrittlement evaluation procedures, the necessity has been shown of introducing modifications in the present surveillance programs aiming at a more precise RPV integrity evaluation facing a possible service life of 60 years. Service life predictions are performed for reactor pressure vessels, based on the available surveillance data, reconstitutioned Charpy specimens and Master Curve testing.